AVM Compartments: Do they modulate trasnidal pressures? An electrical network analysis - Litao, Miguel; Pilar-Arceo, Carlene; Legaspi, Gerardo (Asian Journal of Neurosurgery, 2012)
Background: Arteriovenous malformation (AVM) compartments are thought as independently fed, hemodynamically independent components of the AVM nidus. Its possible role in modulating transnidal pressures have not been investigated to our knowledge. Objective: To investigate if AVM compartments play a role in modulating transnidal pressures by using electrical models as a method of investigation. Materials and Methods: Monocompartmental and multicompartmental AVM models were constructed using electrical circuits- building on Dr. Guglielmi's previous work. Each compartment was fed by two feeding arteries (resistors) and had a shared draining vein with other compartments in the AVM nidus. Each compartment is composed of a series of resistors which represents the pressure gradient along the AVM (arterial, arteriolar, venular, and venous). Pressure (voltage) readings were obtained within these nidal points. Results: The pressure gradient (venous-arterial) is more as there are less AVM compartments in the nidus model. The monocomparmental model had a pressure gradient of 66mmHg (V); while it was 64, 61, and 59 for the 2-, 3-, and 4-compartment models, respectively. In addition, the more the number of compartments, the greater the flow (mA) is in the whole AVM nidus, 33 ml/min for the monocompartmental AVM and 121ml/min for the 4-compartment AVM; though there was greater flow per compartment as there were less compartments, 33ml/min per compartment for the monocompartmental model versus 29ml/min for the 4-compartment model. Conclusion: Transnidal pressure gradients may be less the more compartments an AVM has. This electrical model represents an approach that can be used in investigating the hemodynamic contributions of AVM compartments.
Keywords: Electrical models; hemodynamics; intracranial arteriovenous malformations; nidal compartments